Effects of Graphene, CNT and TiB2 nanoparticles hybridization on morphological structure, dielectric and conductivity of ZnO semiconductors - Macit, Cevher Kursat; Horlu, Merve; Celik, Hilal; Biryan, Fatih; Aksakal, Bunyamin (Elsevier, 2025)
In this study, graphene (Gr)-hybridized carbon nanotubes (CNTs) and titanium diboride (TiB2) nanoparticles were synthesized via the sol-gel method to enhance the dielectric properties and electrical conductivity of zinc oxide (ZnO) semiconductors. The synthesized nanostructures were thoroughly characterized using Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-ray Spectroscopy (EDX), and Raman spectroscopy. The structural influence of CNT and TiB2 hybridization on ZnO, along with the dielectric and conductivity performance of the resulting nanocomposites, was investigated through impedance analysis. The results confirmed the successful synthesis of ZnO, CNT, TiB2, and Gr nanoparticles. Moreover, the dielectric constant and electrical conductivity of the hybrid materials were significantly improved compared to those of pure ZnO nanoparticles. These uniquely engineered nanomaterials are considered promising candidates for applications in solar cells and photovoltaic systems.
Keywords: Nanomaterials; Semiconductor; Carbon nanotube; Titanium diboride; Conductivity